2020
DOI: 10.1101/gr.255273.119
|View full text |Cite
|
Sign up to set email alerts
|

Determining the impact of uncharacterized inversions in the human genome by droplet digital PCR

Abstract: Despite the interest in characterizing genomic variation, the presence of large repeats at the breakpoints hinders the analysis of many structural variants. This is especially problematic for inversions, since there is typically no gain or loss of DNA. Here, we tested novel linkage-based droplet digital PCR (ddPCR) assays to study 20 inversions ranging from 3.1 to 742 kb flanked by inverted repeats (IRs) up to 134 kb long. Of those, we validated 13 inversions predicted by different genome-wide techniques. In a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 68 publications
1
43
0
Order By: Relevance
“…We next focused on likely novel sites of inversion. Our integrated callset contains 100 putatively novel balanced inversions with none or less than 10% reciprocal overlap with events from the prior reports (Sudmant et al 2015;Sanders et al 2016;Audano et al 2019;Chaisson et al 2019;Giner-Delgado et al 2019;Puig et al 2020). These inversions span ~39 Mbp of the genome (Table S7), and five are >1 Mbp in size, including a ~23.2 Mbp pericentromeric inversion on chromosome 2 originating from a Mexican donor (NA19650), with its distal breakpoint lying near (~2 Mbp) the ancestral chromosome 2 fusion point specific to humans (Fig.…”
Section: Inversion Validation and Orthogonal Platform Supportmentioning
confidence: 94%
See 1 more Smart Citation
“…We next focused on likely novel sites of inversion. Our integrated callset contains 100 putatively novel balanced inversions with none or less than 10% reciprocal overlap with events from the prior reports (Sudmant et al 2015;Sanders et al 2016;Audano et al 2019;Chaisson et al 2019;Giner-Delgado et al 2019;Puig et al 2020). These inversions span ~39 Mbp of the genome (Table S7), and five are >1 Mbp in size, including a ~23.2 Mbp pericentromeric inversion on chromosome 2 originating from a Mexican donor (NA19650), with its distal breakpoint lying near (~2 Mbp) the ancestral chromosome 2 fusion point specific to humans (Fig.…”
Section: Inversion Validation and Orthogonal Platform Supportmentioning
confidence: 94%
“…Previously, we and others reported that in the course of primate evolution regions corresponding to disease-associated microdeletions and microduplications at chromosomal regions 15q25,15q13.3,16p12.2,16p11.2,8p23.1,Xq22,17q21.31, as well as at the hemophilia A locus (Xq28) changed their orientation multiple times between a direct and inverted state (Lozier et al 2002;Zody et al 2008;Antonacci et al 2014;Catacchio et al 2018;Maggiolini et al 2019;Maggiolini et al 2020;Puig et al 2020). Based on the presence of inverted repeats with high identity at the boundaries of these regions, we hypothesized that non-allelic homologous recombination (NAHR) increases the probability of recurrent mutations during evolution, a phenomenon that we termed "inversion toggling" (Zody et al 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Conversely, 327 regions (87%), ranging in size from 859 bp to 9 Mbp and amounting to 55.6 Mbp of inverted DNA, were novel and described here for the first time as human/macaque inversions. However, 58 of these 327 regions were previously found to be inverted in Hominidae in a study in which Strand-seq was applied to discover inversions between humans and great apes (Porubsky et al 2020b), and 11 out 327 have been described to be polymorphic inversions in human (Antonacci et al 2009;Chaisson et al 2019;Giner-Delgado et al 2019;Puig et al 2020).…”
Section: Comparison Of Human and Macaque Assemblies And Published Literaturementioning
confidence: 99%
“…1 , Supplemental Figure S1, Additional file 1 ). This is suggestive of genotyping errors because de novo large inversions are thought to arise very infrequently (10 − 5 –10 − 4 /generation [ 18 , 19 ]). We reasoned that two innovations might enable more accurate inversion genotyping.…”
Section: Resultsmentioning
confidence: 99%